Malignant Transformation and Metastatic Spread of Dumbbell-Shaped Meningeal Melanocytoma of the Cervical Spine: A Case Report and Literature Review - Deng, Shuang-lin; Wang, Yu-bo; Wang, Dan-hua; Zhan, Shuang; Jing, Yi; Guan, Yi (Frontiers in Surgery, 2022)
Background: Meningeal melanocytoma is a rare disease that originates from leptomeningeal melanocytes in the central nervous system. Meningeal melanocytoma is generally considered benign, and has a good prognosis following complete surgical resection. Reports of the malignant transformation and spread of these tumors are scarce. Case presentation: A 19 year old female presented with headache, progressive limb weakness, and dyspnea. Magnetic resonance imaging showed a dumbbell-shaped lesion at C1-C2 that was hyperintense on T1 weighted images and showed strong contrast enhancement. Total resection was achieved using a posterior midline approach. Post-operative pathology showed meningeal melanocytoma. The tumor recurred 9 months later with intracranial spread. Resection of the lesion revealed malignant transformation to meningeal melanoma. Conclusion: Meningeal melanocytoma harbors malignant potential even with total resection. Radiotherapy could be considered to prevent disease recurrence and progression.